Can Opposite Clear Corneal Incisions Have a Role with Post-laser In Situ Keratomileusis Astigmatism? - El-Awady, Hatem (Medknow Publications & Media Pvt Ltd, 2012)
PURPOSE: To evaluate the astigmatic correcting effect of paired opposite clear corneal incisions (OCCIs) on the steep axis in patients with residual astigmatism after laser in situ keratomileusis (LASIK) MATERIALS AND METHODS: Thirty-one eyes of 24 patients with a mean age of 28.4 years ±2.46 (range, 19-36 years) were recruited for the study. Inclusion criteria included residual astigmatism of ≥1.5 diopter (D) after LASIK with inadequate residual stromal bed thickness that precluded ablation. The cohort was divided into two groups; group I (with astigmatism ranging from -1.5 D to -2.5 D) and group II (with astigmatism > -2.5 D). The steep axis was marked prior to surgery. Paired three-step self-sealing opposite clear corneal incisions were performed 1-mm anterior to the limbus on the steep axis with 3.2-mm keratome for group I and 4.1 mm for group II. Patients were examined 1 day, 1 week, 1 month, 3 months and 6 months, postoperatively. Visual acuity, refraction, keratometry, and corneal topography were evaluated preoperatively and postoperatively. Analysis of the difference between groups was performed with the Student t-test. P<0.05 was considered statistically significant. RESULTS: The mean uncorrected visual acuity (UCVA) improved from 0.35±0.13 (range, 0.1-0.6) to 0.78±0.19 (range, 0.5-1) in group I and from 0.26±0.19 (range, 0.1-0.5) to 0.7±0.18 (range, 0.4-1) in group II. The increase in UCVA was statistically significant in both groups (P=0.001, both cases). The mean preoperative and postoperative keratometric astigmatism in group I was 2.0±0.48 D (range, 1.5-2.5 D) and 0.8±0.37 D (range, 0.1-1.4 D), respectively. The decrease in keratometric astigmatism was highly statistically significant in group II (P=0.001.). Mean surgically induced astigmatic reduction by vector analysis was 1.47±0.85 D and 2.21±0.97 D in groups I and II respectively. There were no incision-related complications. CONCLUSIONS: Paired OCCIs were predictable and effective in correcting post-LASIK astigmatism and required no extra surgical skill or expensive instruments. OCCIs are especially useful in eyes with insufficient corneal thickness for LASIK retreatment.